Arahan Pengembangan Ruang Terbuka Hijau (RTH) Berdasarkan Tingkat Kenyamanan Termal di Kecamatan Sukajadi Kota Bandung - Fadia Anzira Yasmin; Tonny Judiantono; Verry Damayanti (UNISBA Press, 2023)
Abstract. Temperature Humidity Index (THI) is an indicator that can determine the level of thermal comfort in which the sensation of thermal comfort is received by people in an urban area. The situation and atmosphere in Sukajadi District can be said to lack climate control media, so that when the temperature is high it will feel very hot and arid. The existing green open space in Sukajadi District is only available for 2.7% of the total area which is due to limited land and space. The temperature in Sukajadi District is at an average temperature of 27.8°C – 30.5°C. The purpose of this study is to provide directions and recommendations for the development of green open space to achieve thermal comfort standards in Sukajadi District. The methods used are Normalized Difference Vegetation Index (NDVI), Urban Heat Island (UHI), Temperature Humidity Index (THI), calculation of green open space needs based on THI, and formulation of green open space development directions using a qualitative descriptive method. The results of this study are that Sukajadi District has a THI value of 25-29, belonging to two classes, namely some are uncomfortable and some are uncomfortable. Provision of green open space to achieve thermal comfort of 43.03 Ha. There are alternative ways to obtain land that has the potential to become green open space, namely land consolidation and acquisition of private green open space by planting vegetation that can reduce temperature and protect from sun exposure. Abstrak. Temperature Humidity Index (THI) merupakan suatu indikator yang dapat menentukan tingkat kenyamanan termal yang dimana sensasi dari kenyamanan termal diterima oleh masyarakat di suatu wilayah perkotaan. Keadaan dan suasana di Kecamatan Sukajadi bisa dikatakan kurang adanya media pengatur iklim, sehingga di kala suhu sedang tinggi akan dirasa sangat panas dan gersang. RTH eksisting yang ada pada Kecamatan Sukajadi hanya tersedia sebesar 2,7 % dari luas wilayah yang dimana luas wilayah akibat keterbatasan lahan dan ruang. Suhu di Kecamatan Sukajadi berada pada rata – rata suhu sebesar 27,8°C – 30,5°C. Tujuan penelitian ini yaitu memberikan arahan dan rekomendasi pengembangan RTH untuk mencapai standar kenyamanan termal di Kecamatan Sukajadi. Metode yang digunakan yaitu Normalized Difference Vegetation Index (NDVI), Urban Heat Island (UHI), Temperature Humidity Index (THI), perhitungan kebutuhan RTH berdasarkan THI, dan perumusan arahan pengembangan RTH dengan metode deskriptif kualitatif. Hasil dari penelitian ini yaitu Kecamatan Sukajadi memiliki nilai THI sebesar 25-29, termasuk ke dalam dua kelas yaitu sebagian tidak nyaman dan tidak nyaman. Penyediaan RTH untuk mencapai kenyamanan temal sebesar 43,03 Ha. Terdapat cara alternatif untuk mendapatkan lahan yang berpotensi menjadi RTH yaitu konsolidasi lahan dan akuisisi RTH privat dengan dilakukan penanaman vegetasi yang dapat mereduksi suhu dan melindungi dari paparan sinar matahari.